Japan : a concise history - Meyer, Milton Walter (Rowman & Littlefield, 2009)
The emergence of Japan as a political and economic global power has been one of the most remarkable success stories of modern history. Though small in geographic area, the archipelago is the tenth most populous country, with 128 million inhabitants crowded into an area the size of Montana. Its natural resources are almost nonexistent, yet today it ranks only second after the much larger United States as the most affluent and economically productive nation in the world. Its rich cultural heritage and high-tech society are equally vibrant. For all readers wanting to better understand this dynam.